NEOTECTONIC DEVELOPMENT OF THE ÇAMELI BASIN, SOUTHWESTERN ANATOLIA, TURKEY - Alçiçek M.C.; Özkul M.; Ten Veen J.H. (My University, 2006)
This study of the Çameli Basin presents a detailed basin evolution combined with structural analysis and provides the first detailed time-stratigraphic framework for the neotectonic development of Neogene grabens along the Fethiye-Burdur Fault Zone in southwestern Anatolia. During the Early Tortonian, the Çameli Basin was established as a broad fault-bounded fluviolacustrine basin that experienced NW-SE extension. By Mid-Pliocene time, continued NW-SE extension resulted in the formation of a new intrabasinal fault zone that split the basin longitudinally into two compartments. The development of a new generation of normal faults further split the basin into four narrow half-graben compartments at the end of the Late Pliocene. Structural analysis of basin-bounding and intrabasinal faults related to this three-stage basin development shows that NW-SE extension apparently persisted from Late Miocene to early Quaternary time. The youngest (i.e. Holocene), deformation is characterized by dextral shear along NE-SW-trending strike-slip faults and continuing NW-SE extension. The Late Miocene foundering of the basin was related to extension in the northerly hinterland zone of the still-emplacing Lycian nappes, whereas outward growth of the Hellenic Arc in response to the westward Anatolian extrusion is the main cause for NW-SE extension from the Pliocene onward. Dextral strike-slip faulting is localized and is associated with the activity of NW-SE-trending faults that accommodated NE-SW extension. The simultaneous activity of these faults suggests the existence of biaxial extensional tectonics, as initially proposed for the Burdur-Dinar area. Sinistral strike-slip faulting, continuing along the eastern Hellenic Arc, penetrated the southernmost part of Turkey but has not yet reached the Çameli Basin area. Our biostratigraphically well-constrained tectonosedimentary model for the evolution of the Çameli Basin provides a reliable time-stratigraphic framework for NE-SW extension in the 'Fethiye-Burdur Fault Zone' of SW Anatolia. We believe that this fault zone represents a broad zone of isolated or interconnected NE-SW-trending basins that formed under prevailing NW-SE extension, rather than being a significant strike-slip fault zone. © The Geological Society of London 2006.
Keywords: Holocene; Pliocene; Tortonian; Cenozoic::Quaternary::Holocene; Кайнозой::Четвертичная::Голоцен; Cenozoic::Neogene::Pliocene; Кайнозой::Неоген::Плиоцен; Cenozoic::Neogene::Miocene::Tortonian; Кайнозой::Неоген::Миоцен::Тортонский